Dual effect of aucubin on promoting VEGFR2 mediated angiogenesis and reducing RANKL-induced bone resorption - Yulin He; Hiotong Kam; Xue Wu; Qian Chen; Simon Ming Yuen Lee (BMC, 2023)
Abstract Background Angiogenesis is regarded as a critical role in bone repair and regeneration, involving in pathological bone disorders such as osteoporosis. Aucubin, an iridoid glycoside primarily derived from Eucommia ulmoides, is reported to inhibit osteoclast activity, enhance bone formation and promote angiogenesis in osteoporosis models. Our study is to further investigate the anti-osteoporosis effect of aucubin in transgenic medaka, and the pro-angiogenic effect of aucubin and its mechanism of action both in vivo and in vitro. Methods The anti-osteoporosis effect of aucubin was confirmed by using RANKL-stimulated bone resorption transgenic medaka. The pro-angiogenic effect of aucubin in vivo was investigated using vascular endothelial growth factor (VEGF) tyrosine kinase inhibitor II (VRI)-induced vascular insufficient transgenic zebrafish model. Furthermore, endothelial cell proliferation, migration, tube formation and the mechanisms were evaluated to identify the pro-angiogenic effect of aucubin in normal and su5416-injured human umbilical vein endothelial cells (HUVECs). Results Aucubin decreased the resorption of the mineralized bone matrix and centra degradation in heat-shocked transgenic col10α1:nlGFP/rankl:HSE:CFP medaka. Moreover, aucubin reversed VRI-induced vascular insufficiency in zebrafish through regulating flt1, kdr, kdrl, vegfaa, ang-1, ang-2, tie1 and tie2 mRNA expressions in Tg(fli1a:EGFP)y1 or AB wild type zebrafish. Aucubin promoted cell proliferation by upregulating p-mTOR, p-Src, p-MEK, p-Erk1/2, p-Akt and p-FAK in HUVECs. Furthermore, aucubin exhibited a pro-angiogenic effect on su5416-injured HUVECs by promoting their proliferation, migration, and tube formation through regulating the phosphorylation of VEGFR2, MEK, ERK and the ratio of Bcl2-Bax. Conclusion Aucubin could reduce bone resorption in RANKL-induced osteoporosis medaka by live imaging. Meanwhile, aucubin exhibited a protective effect in VRI-induced vascular insufficient zebrafish by regulating VEGF-VEGFR and Ang-Tie signaling pathways. Additionally, aucubin promoted the proliferation, migration and tube formation of HUVECs probably by mediating VEGFR2/MEK/ERK, Akt/mTOR and Src/FAK signalling pathways. This study further indicated the dual effect of aucubin on angiogenesis and osteogenesis which may be beneficial to its treatment of osteoporosis.